2021
DOI: 10.1002/smll.202006433
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic Effects on Electrochemical Performance of Conversion‐Based MnO2 Anode Materials for Next‐Generation Li Batteries

Abstract: In this study, four different MnO2 polymorphs are synthesized with a controlled morphology of hollow porous structures to systematically investigate the influences of polymorphs in conversion‐based material. As the structure of these materials transforms into nanosized metal and maintains an extremely low‐crystalline phase during cell operation, the effects of polymorphs are overlooked as compared to the case of insertion‐based materials. Thus, differences in the ion storage behaviors among various MnO2 polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 78 publications
(107 reference statements)
1
12
0
Order By: Relevance
“…Lithium-ion batteries (LIBs) with high energy density have been regarded as one of the prominent devices to meet the demand of portable electronic devices and electric vehicles. [1][2][3][4][5][6][7] the tensile hoop stress arising from the volume variation. And carbon not only greatly enhances electron transport but also boosts mechanical robustness.…”
Section: Introductionmentioning
confidence: 99%
“…Lithium-ion batteries (LIBs) with high energy density have been regarded as one of the prominent devices to meet the demand of portable electronic devices and electric vehicles. [1][2][3][4][5][6][7] the tensile hoop stress arising from the volume variation. And carbon not only greatly enhances electron transport but also boosts mechanical robustness.…”
Section: Introductionmentioning
confidence: 99%
“…During subsequent charging, the Na 2 Se peaks were gradually reduced, and NiSe 2 peaks were observed again after complete charging, indicating the reversibility of the conversion reaction [22]. Similarly, other researchers have proven the conversion reaction mechanism using XRD techniques by observing the metallic phase and LiX/NaX phases after full discharge [23][24][25][26][27][28]. However, although XRD is a powerful method for obtaining phase-sensitive information, it is not always the best choice for identifying conversion reactions because most conversion-based materials significantly lose their crystallinity during lithiation.…”
Section: Ion Storage Reaction Mechanismmentioning
confidence: 75%
“…To explore the effects of polymorphs, H. Kim et al systematically investigated the charge storage behaviors of four different MnO 2 polymorphs possessing similar hollow porous morphology, as shown in Fig. 10(a) [24]. The voltage profiles of the four samples in Fig.…”
Section: Polymorph Controlmentioning
confidence: 99%
“…[1][2][3][4] In addition, owing to the different linking patterns of the [MnO 6 ] octahedral units, the MnO 2 structure exhibits a high degree of polymorphism featuring one-dimensional tunnel configurations in majority, [5] which greatly facilitate reversible charge transport and storage in MnO 2 and enables its use as electrode materials in rechargeable batteries. [6,7] Yet, the extensive application of MnO 2 for reversible energy storage is still in its infancy due to the existing drawbacks of MnO 2 materials, among which stands out the notorious fast capacity decay of MnO 2 electrode upon longterm cycling. [8,9] The rechargeability of tunnel-structured MnO 2 has been tested since two decades ago, led by Thackeray et al at Argonne National Laboratories, whose finding revealed a moderate first-cycle capacity ( % 180 mAh g À1 ) followed by quick capacity fading during the rest cycles.…”
mentioning
confidence: 99%